Ectoparasites of dogs in home environments on the Caribbean slope of Costa Rica - Alvarado, Gilbert (2012)
Reports on ectoparasites on dogs in Central America are scarce. The aim of this study was to identify flea, louse and tick species infesting dogs in home environments on the Caribbean slope of Costa Rica, and determine their frequency and coexistence. Ectoparasites were collected from dogs in 83 rural homes at five study sites. Specimens were identified and separated according to species. Fleas were the most common ectoparasite (G = 22,217, DF = 8, p = 0.004). Ctenocephalides felis and Pulex simulans were found in 83% and 55% of the homes with ectoparasites, respectively. Trichodectes canis (13%), Heterodoxus spiniger (10%), Rhipicephalus sanguineus (18%), Rhipicephalus (Boophilus) microplus (5%) and Amblyomma ovale (8%) were also present. More than one species was collected in most cases (66%), and the most common combination was C. felis and P. simulans (59% of homes with fleas). The high frequency of P. simulans emphasizes the need for adequate identification. This was the first study involving different ectoparasites of dogs in Costa Rica, as well as the first report of T. canis in this country. The relative frequency and coexistence of these ectoparasites in the home environment may have implications for animal and human health.